‘Emotiplay’: a serious game for learning about emotions in children with autism : results of a cross-cultural evaluation - Fridenson-Hayo, Shimrit; Bölte, Sven (European child & adolescent psychiatry, 2017)
Children with autism spectrum conditions (ASC) experience difficulties recognizing others’ emotions and mental states. It has been shown that serious games (SG) can produce simplified versions of the socio-emotional world. The current study performed a cross-cultural evaluation (in the UK, Israel and Sweden) of Emotiplay’s SG, a system aimed to teach emotion recognition (ER) to children with ASC in an entertaining, and intrinsically motivating way. Participants were 6-9 year olds with high functioning ASC who used the SG for 8-12 weeks. Measures included face, voice, body, and integrative ER tasks, as well as parent-reported level of autism symptoms, and adaptive socialization. In the UK, 15 children were tested before and after using the SG. In Israel (n = 38) and Sweden (n = 36), children were randomized into a SG or a waiting list control group. In the UK, results revealed that 8 weeks of SG use significantly improved participants’ performance on ER body language and integrative tasks. Parents also reported their children improved their adaptive socialization. In Israel and Sweden, participants using the SG improved significantly more than controls on all ER measures. In addition, parents in the Israeli SG group reported their children showed reduced autism symptoms after using the SG. In conclusion, Emotiplay’s SG is an effective and motivating psycho-educational intervention, cross-culturally teaching ER from faces, voices, body language, and their integration in context to children with high functioning ASC. Local evidence was found for more generalized gains to socialization and reduced autism symptoms.
Gesehen am 05.11.2018